Changes in plasma and urinary taurine and amino acids in runners immediately and 24h after a marathon - Cuisinier, C.; Ward, R. J.; Francaux, M.; Sturbois, X.; de Witte, P. (Amino Acids, 2001)
Changes in urinary and plasma taurine and amino acids have been evaluated in trained runners competing in the Rotterdam Marathon, 1998, both immediately after completing the event and 24h after recovery. There were significant changes in the urinary amino acids excretion, the majority showing a significant decrease both immediately at the completion of the Marathon and after 24h recovery. In contrast urinary taurine excretion increased immediately post Marathon, although not significantly as the range of results was wide. Such changes in urinary taurine correlated with percentage changes in plasma creatine kinase both immediately post race, (r = 0.972, P < 0.001), and 24h later (r = 0.872, P < 0.001), possibly indicating that the source of the taurine was muscle. Significant correlations between the individual values for urinary and plasma amino acids in all of the athletes were calculated for taurine (r = 0.528), glycine (r = 0.853), threonine (r = 0.749), alanine (r = 0.747), serine (r = 0.620), glutamine (0.614), arginine (r = 0.507), histidine (r = 0.470) and valine (r = 0.486). Changes in the mean plasma concentrations of amino acids were comparable to our previously published data (Ward et al., 1999) the majority showing significant decreases immediately and 24h post Marathon, such an adaptation being due primarily to their utilisation for gluconeogenesis. However, in contrast, the mean taurine concentrations were significantly elevated both post race, P Z 0.01 and after 24h, P < 0.05. The physiological response by the muscle to exhaustive exercise, particularly with regard to changes in plasma and urinary taurine concentrations remain to be elucidated, but is probably related to muscle function impairment. The increase in taurine urinary excretion could be used as an indicator of muscle damage occurring during exhaustive exercise. Whether taurine supplementation would minimise such changes is an interesting scientific question and merits investigation.